(untitled) (American Journal of Islam and Society, 2018)
Anyone familiar with Bruce Lawrence’s oeuvre knows that the book under review is the culmination of his long and serious engagement with Islam’s foundational texts. His earlier publication, The Qur’an: A Biography (2006), traces the central place of divine revelation in Muslim life and thought for many centuries. The Qur’an inspired its most faithful believers to become predominant in much of the medieval world and, in the process, it was a book that captured the interest and imagination of non-Muslims. Law- rence’s own translation of the Qur’an into English is now in the works. Be- fore completing this admirable feat at the prime of his scholarly life, he offers us an inventory of a number of influential and no less creative—some polemical—attempts at untying the Gordian knot of rendering classical Ar- abic into lucid English. But can God’s eternal word, revealed to Prophet Muhammad in the seventh century, be translated into English at all given the deep-seated differences between the two linguistic worlds in space and time? The answer to this question is not a simple yes or no, as Lawrence explains in this slim but indispensable volume. Unlike scriptures of other world religions, the Qur’an stakes a claim on its linguistic authoritativeness from the onset. Its self-image, as specialists such as Daniel Madigan, Toshi- hiko Izutsu, and Fazlur Rahman have it, was rooted in its unique language. The Qur’anic language is thus not merely one language among others of its time (or anytime) but is the distinctive language of God to be read, stud- ied, memorized and disseminated in the original form. From this angle of vision, no translation of the Qur’an is regarded by the majority of Muslims as the Qur’an itself. Lawrence acknowledges this longstanding credo, or the dominant “filter of orthodoxy,” as he puts it (xxi). The translated Qur’an is, to him, best referred to as a “Koran”. Not that the Arabic and translated texts are radically different in terms of their central messages and moral injunctions, but that the Koran was a historical and not an eternal artefact. The Koran was a product of a human endeavor to make the language of God accessible in the world of man. The filter of orthodoxy was however confronted with an ever-growing and cosmopolitan ummah which, for the most part, consisted of non-Ar- abs who knew little but a rudimentary form of Arabic. Translations became inevitable, as Lawrence informs us. The Arabic Qur’an in its pure form gen- erated Korans in other Muslim languages (Persian, Turkish, Malay, etc.) as Islam grew to become a juggernaut after the death of Muhammad (Chapter 1). And yet, as Islam emerged triumphant as a world-conquering faith, its adversaries saw the urgent need to fully discern the scriptures that made Muslims so powerful. Translations into Latin and then English from the twelfth through the eighteenth centuries were largely born out of hate en- meshed with fear and the passionate desire among translators to convince fellow Christians of “falsehood of the Qur’an” (33). Such adverse motives however turned into an emphatic understanding of what the Qur’an actu- ally stood for, as seen in George Sale and Edward Henry Palmer’s transla- tions. The Orientalists were not all cut from the same cloth. What Lawrence does not show quite clearly was how these early English translations provided the raison d’etre for Muslims to produce their own Korans as a corrective project against the biases of Western Orientalism. In South Asian translations by Muhammad Ali, Abdul Majid Daryabadi, Mar- maduke Pickhall, and Abdullah Yusuf Ali, allusions were made, be it direct- ly or obliquely, to the problems of earlier (non-Muslim) translations, just as they sought (for example) to undo use of the terms “Mohammedan” or “Mohametan” to describe Muslims. Granted that these translators belonged to different Muslim sects, their overriding concern was that the Qur’an suf- fered from imprecise translations into English. South Asian Muslims, in my view, were not only translating the Qur’an. They were arresting the march of a prejudiced form of Orientalism by producing English Korans of their own. In hindsight, their efforts were successful, at least for a while, until the advent of the digital age. The coming of the internet and the expansion of English as a lingua franca of most of the world, as Lawrence handsomely points out, has led to the proliferation of Korans, both online and offline, by Muslims and non-Muslims, conservatives and liberals, orientalists and their detractors, Sunnis and Shi’ites, feminists and artists. To Lawrence, most translations produced in an era of abundance fail to capture the Qur’an’s rhythmic prose, with the exception of a handful. Contemporary Korans are so often contorted by the politics of ideological hegemony and nationalist parochi- alism that hinder scholarly endeavor (Chapters 4-5). Lawrence singles out Saudi translations that purvey a puritanical strand of Islam. Interestingly, there are, within Saudi Arabia itself, less literalist Korans. One wonders whether the current political transition in Saudi Arabia will give rise to newer, state-sponsored translations of the Qur’an. I certainly believe it will. For now, Lawrence shows that Salafism in Saudi Arabia (as elsewhere in the Muslim world, as many analysts have pointed out) is not by any means monochrome and homogenous. It is therefore unsurprising that different Korans have been produced in a highly controlled and conservative state. Meantime, the market is flooded with highly popular alternatives in the likes of those by Thomas Cleary, Muhammad Abdul Haleem, and Tarif Khalidi. Spoilt for choice, Muslims and non-Muslims have now the liberty to choose which translation squares with their respective lingustic tastes, spiritual quests, and worldviews. Lawrence ends the book with the latest and most innovative venture at translating the Qur’an, by artist Sandow Birk. It is a translation that comes in the form of inventive expressions, a graphic Koran, so to speak, intended for an American audience whom Birk believes can discern how the Qur’an addresses their everyday trials and tribulations. The linguistic beauty of the Qur’an, in Birk’s formulation, is best expressed in colorful images. An American himself, Lawrence is most impressed by Birk’s project, couching it as “visual and visionary, it is a hybrid genre designed to reach a new audience not previously engaged either by the Koran or by Islam” (137). Had George Sale and Henry Palmet lived to this day, they would perhaps shudder over such an Americanization of the Qur’an. In displaying art with a Qur’anic glaze, Birk does more than translating the Qur’an to English. He demonstrates how the Qur’an can be embedded and normalized into Anglo-American lives and sensibilities. Provocatively-written, deftly-researched, and a pleasure to read, The Koran in English opens up many promising pathways and novel directions for future research. The specter of the Palestinian-American scholar, Is- mail al-Faruqi, came to mind as I was reading the book. Al-Faruqi once envisioned English becoming an Islamic language, or a language that can express what Islam is more accurately. Al-Faruqi held that this could be achieved by incorporating Arabic terms into the English corpus. Reading The Koran in English tells us that Al-Faruqi’s vision is currently realized in ways he barely imagined, or perhaps, in ways that are more subtle and sublime. In translating the Koran to English—an enterprise that is now undertaken by scholars, popular writers, and artists, and that will undoubt- edly grow exponentially in the years to come—English has been (or is) Ko- ranized. Or, to borrow and inflect Lawrence’s syllogism in the opening of the book: If you don’t know Arabic, you can still understand the Qur’an. By understanding the Qur’an, you can choose to become a Muslim. And if you do not become a Muslim, you may still appreciate and derive much benefit from the Qur’an. Therefore, the Qur’an, or the Koran, is not only for Muslims but for those who care to think and reflect about life and about the divine. Indeed, “He gives wisdom to whom He wills, and whoever has been given wisdom has certainly been granted much good. And none will grasp the message except the people of intellect” (al-Baqara: 269). Khairudin Aljunied Malaysia Chair of Islam in Southeast Asia Georgetown University